2000
DOI: 10.1016/s0042-6989(99)00170-4
|View full text |Cite
|
Sign up to set email alerts
|

The magnocellular deficit theory of dyslexia: the evidence from contrast sensitivity

Abstract: A number of authors have made the claim that dyslexia is the result of a deficit in the magnocellular part of the visual system. Most of the evidence cited in support of this claim is from contrast sensitivity studies. The present review surveys this evidence. The result of this survey shows that the support for the magnocellular deficit theory is equivocal. In the case of spatial contrast sensitivity there clearly are results that are consistent with the magnocellular deficit theory; however, these results ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
176
3
12

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(200 citation statements)
references
References 65 publications
6
176
3
12
Order By: Relevance
“…Consequently impairment of the dorsal stream or the magnocellular system has been implicated following reports of high motion coherence thresholds (Atkinson et al, 1997;Hansen et al, 2001;Milne et al, 2002;Spencer et al, 2000;Stein & Walsh, 1997). However, others have challenged the inference of a purely magnocellular impairment from high motion coherence thresholds (Bertone et al, 2003;Skottun, 2000), and, as was noted in the Introduction, there is no direct physiological evidence of magnocellular abnormality in autism. Recent research has highlighted the influence of attention in early vision such as stereoscopic depth (Rose, Bradshwaw, & Hibbard, 2003) and motion perception (Chaudhuri, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently impairment of the dorsal stream or the magnocellular system has been implicated following reports of high motion coherence thresholds (Atkinson et al, 1997;Hansen et al, 2001;Milne et al, 2002;Spencer et al, 2000;Stein & Walsh, 1997). However, others have challenged the inference of a purely magnocellular impairment from high motion coherence thresholds (Bertone et al, 2003;Skottun, 2000), and, as was noted in the Introduction, there is no direct physiological evidence of magnocellular abnormality in autism. Recent research has highlighted the influence of attention in early vision such as stereoscopic depth (Rose, Bradshwaw, & Hibbard, 2003) and motion perception (Chaudhuri, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…[183][184][185][186][187] The studies supporting this theory are outnumbered by studies that have found no loss of contrastsensitivity and other studies that have found contrast-sensitivity reductions or other findings inconsistent with a magnocellular deficit. [188][189][190][191][192][193][194][195][196][197][198][199][200][201] Thus, the evidence in support of the magnocellular theory is equivocal at best. Amitay et al 191 found that although some (6 of 30) subject with dyslexia showed impaired magnocellular function, they consistently showed impaired performance in auditory and nonmagnocellular visual tasks.…”
Section: Magnocellular Deficit Theorymentioning
confidence: 99%
“…Although numerous studies have investigated the spatial frequency sensitivities shown by dyslexic and non-dyslexic readers (for a review, see Skottun, 2000), the effectiveness of the spatial frequency content of text for fast and slow skilled adult reading remains to be revealed. So far, direct information on this issue has been provided by Patching and Jordan (2005a) and their findings suggest that briefly-presented single words, filtered to contain only certain spatial frequencies, are identified equally accurately by fast and slow readers.…”
mentioning
confidence: 99%